Knowing the shape of the physical identity of the city - Heyder Kamel , Noor; Ehsan Shok , Mufeed (Journal of Planner and Development, 2022)
This  research deals with the form of the physical identity which is concerned with the features and characteristics that distinguish the shape of the city from other existing cities and reveal its similarity with the self (itself) and objective difference with others.  Accordingly, these features must be sophisticated and variable resulting the shape of the city, while preserving the continuity of time, and eventually leads to the emergence of the whole shape. Physical identity is conceptually equivalent with the terms "personality" and "sense of place".  The research determined the criteria for evaluating the physical identity as follows:                        • Distinction / similarity, in the sense of distinction from the other and similarity with the self.• Continuity/transformation, means linking to the past and uninterrupted (continuity of subjective meaning and values) and at the same time innovation and creativity according to the circumstances of their time (they remain the same without remaining as they were.)• Unity/pluralism, the connection between different, heterogeneous and even contradictory components to form a whole together. Contextual and regional theories are the theoretical basis for interpreting and explaining the above criteria in the fields of architecture and urban design, and follow a descriptive analytic approach.